Aspen Dynamics simulation of a middle-vessel batch distillation process. (September 2015) - Luyben, William L.
Highlights: Aspen simulation used to simulate the batch middle-vessel process. Equipment sizes and stream connections established in steady-state Aspen Plus. Batch dynamic transients using Aspen Dynamics. Abstract: Aspen Dynamics is a powerful dynamic simulator that is widely used to explore the dynamics and control of continuous processes around some steady-state design operating point. This paper explores its use to study the dynamics of a batch process. The example studied is a middle-vessel batch distillation system for separating a ternary mixture. The batch system is operated by adjusting the two reflux flowrates (one from the reflux drum to the top of the upper column and the second from the middle vessel to the top of the lower column). The liquid inventories in the three drums vary with time. This paper shows how this batch operation can be conveniently simulated by first using the steady-state simulator Aspen Plus to correctly size the equipment. Then the file is exported into Aspen Dynamics where a rigorous dynamic simulation can explore alternative control strategies by using the large library of control functions.